(untitled) (Fiep Bulletin - online, 2014)
So that the physical exercise can carry out a beneficial effect to the veined system is fundamental that this doesn’t overload the valve apparel excessively. The study had as objective analyzes the effects of exercises program neuromuscular on the veined diameter of the greater and short saphenous vein of the inferior limbs, which elapses of a study experimental, longitudinal, accomplished with 20 individuals, with average of (21,30±3,16) years old, distributed in two groups: Practicing G1 of Muscular activity and G2 Control Group, composed by six women and four men and three men and seven women respectively. It was used color-flow Doppler to measure the diameters of saphenous veins. Soon afterwards, the volunteers were submitted to practice exercises by four months, frequently weekly of three days, lasting 60 min, in muscular activity machines and free weights, alternate for segments, with three series of 12 repetitions and intervals of 40seg, with heating of 10min. The group control didn’t practice regular physical activities. When appraised the diameters of G1, it was observed that the examined veins came competent after the training period, and when compared the first with the second exam weren’t found significant differences in any measurement point. G2, when appraised presented significant differences in three points of gauging of diameters: superior third of the right thigh (p=0,004), left thigh’s superior third (p=0,013) and inferior third of the left leg (p=0,012). In spite of the measure of the diameters be larger in the second exam, the veins were classified as competent for not present sanguine ebb. The results concluded that the muscular activity didn’t affect the structure of the veins, once they were classified as competent and people that don’t practice activities tend to have an increase in the diameter of the veins.